Henri Cartier-Bresson: The Decisive Moment Elliott Erwitt: Pittsburgh 1950. (Afterimage, 2018)
The article reviews the photography exhibition "Henri Cartier-Bresson: The Decisive Moment Elliott Erwitt: Pittsburgh 1950" displaying the works of photographer Henri Cartier-Bresson, held at the International Center of Photography in New York City on May 23-September 2, 2018.